الاستحسان عند الحنفية وتطبيقو في عقد البيع )دراسة تٖليلية مقارنة(قدمت ىذه الرسالة استكمالا ت١تطلبات نيل درجة ات١اجستتَ الشريعةالإسلبمية جامعة سوراكرتا المحمديةAl-Istihsan According To Madzhab Hanafiya And It's Application In The Contract Of Sale (Comparative Study) - Mutaqin, Zainal; , Dr.Muindinillah Basri, M.A (2013)
"Istihsan" has special position in Islam law and play an important role to solve all stors of laws when " Qiyas" can't be used . Although, a ser ios debating about istihsan's definition and a problem abaut permission to use istuhsan becomes the basic of the low, but finally, they agree with this function however they have different understanding. The group of "ulama" that practice " Istihsan" is Hanaiya seet, they have very good ability in practice istihsan o for solve many lows of fiqih temporary that can't be qiyas do, especially on baying and selling problem. Istihsan be legal basic for keeping human rights in economic activity. So, That Istihsan is keep this " Syari'at" be able to legal basic that appropriated the times. As the result, the writer finds the different between madzhab Hanafiya and syafiiya about Istihsan , and how to use it to contract of sale.